Pengaruh Religious Altruism Dan Religious Enrichment Terhadap Keputusan Pembelian Produk UMKM Oleh Muslim Di Kota Pekanbaru - Nurrahmi Hayani; Sri Murhayati; Darni Darni; Abdiana Ilosa (ITB AAS INDONESIA Surakarta, 2023)
This study aims to determine the effect of religious altruism and religious enrichment on the purchasing decisions of MSME products by Muslims in Pekanbaru City. This study used purposive non-random sampling of 269 respondents and used primary data and secondary data. The data analysis method used is multiple linear regression method. This study found that Religious Altruism and Religious Enrichment have an influence on the purchasing decisions of SMEs products by Muslims in Pekanbaru either partially or simultaneously. These two variables have an influence of 0.483 or 48.3% on the purchasing decision variable while the remaining 51.7% is influenced by other factors not discussed in this study. This study uses a data collection method in the form of a questionnaire distributed online (google form). So it is advisable to group respondents based on generational characteristics (X, Y and generation Z.